CORPORATE SOCIAL RESPONSIBILITY AS AN INSTRUMENT OF INCREASING COUNTRY COMPETITIVENESS - Brin, Pavlo; Nehme, Mohamad; Polančič, Gregor (Torun International Studies, 2020)
The integration process of Ukraine into the European Union requires fundamental changes in economic, social, and environmental spheres. The provision for any significant changes should be based on a deep investigation. Corporate Social Responsibility is regarded nowadays as a critical factor for the change management process in economic, social, and environmental spheres. In the present paper, an investigation on Corporate Social Responsibility, as perceived in the European Union in general, and in Ukraine in particular, has been made. The article has been based on the comparison of the data between Ukraine and other European Union countries. Challenges for Corporate Social Responsibility development in Ukrainian corporations have been addressed, followed by a set of recommendations to ensure effective fundamental changes in the integration process through CSR activities.